Evaluasi Pelaksanaan Kurikulum 2013 Di Pondok Pesantren Manahijussadat Banten - Anas Fauzi; Fauzan (Edukasiana: Journal of Islamic Education, 2023)
Abstract The curriculum has an important role in the quality of education. Curriculum implementation in Indonesia is centered on the government but is the authority of each madrasah, because this type of curriculum implementation model, which is called top down up, is used in our country. The 2013 curriculum is now a reference that is considered effective for student behavior, so the government will implement it in all educational institutions in Indonesia, both public and private schools. Madrasah are private schools under the auspices of the department of religion, often madrasah are neglected by the government's appreciation, but we need to know that madrasah have carried out many innovations and evaluations of the 2013 curriculum. In this way the author discusses things that can be evaluated on factors that support the implementation of the curriculum 2013 at the Manahijussadat Islamic Boarding School, especially at the Manahijussadat Islamic Boarding School Madrasah Aliyah. In this research, researchers used qualitative descriptive methods with data collected using participant observation, in-depth interviews and documentation. This research resulted that an evaluation of curriculum implementation at the Manahijussadat Islamic boarding school was carried out covering aspects of teacher preparation, facilities and infrastructure, principal management, school environment, community and financing. Curriculum evaluation on these aspects has been carried out well and the evaluation results are used as a basis for improving the quality of the learning curriculum for the next school year.